On Refusal Strategies in Modern English - Karapetyan, Sirarpi (Armenian Folia Anglistika, 2009)
The article examines refusal strategies in English, especially the ones which follow speech acts expressing a request. The investigation is carried out along the lines of the interaction of refusal and request in Modern English. Through a detailed study of the more frequent types of refusal strategies in the process of communication the author tries to reveal and analyze the complicated and interesting relation between refusal and request.